A wide water ratio undisturbed phosphogypsum composite curing agent for road base replaceable gravel aggregate, a road base material and a preparation method thereof

CN122878103APending Publication Date: 2026-10-09CHONGQING JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610767919.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

原状磷石膏含水率波动范围宽、整体偏高(含水率15%~30%),颗粒超细、比表面积大、亲水性强,且内部富含可溶性硫酸盐、磷酸盐及氟化物,如果将其直接用于道路工程,存在以下缺陷:高含水状态下易饱和软化,碾压施工易形成弹簧土,压实度难以满足公路基层规范要求;现有技术中也有采用固化剂稳定磷石膏,但是单一水泥、石灰这些固化剂功能单一,仅能提升早期强度,无法破除磷石膏颗粒表面连续水膜,抗滑移、抗回弹能力差;且体系内硫酸盐易引发后期体积膨胀、路面起鼓开裂,长期安定性不足;同时还存在耐水性能差,遇水浸泡易软化溃散的问题

Benefits of technology

[0018]本发明的有益效果: 本发明的用于道路基层可替代砂石集料的宽水率原状磷石膏复合固化剂、道路基层材料及其制备方法,通过矿渣粉、消石灰、无水硅酸钠、粉煤灰构成碱-矿渣基础胶凝体系,为固化体提供长期强度增长骨架,以早强固凝剂、增强剂、体积稳定剂、界面疏水剂、填料、纳米晶核诱导剂和施工性能调节剂进行复合改性,共同构建“碱性激发-快速固磷-多级填充-精准抑胀-界面疏水-施工调控”的复合功能体系,协同增效,实现高含水原状磷石膏免烘干、免加砂石的直接资源化利用,解决高含水原状磷石膏直接用于道路基层时存在的强度不足、耐水差、易膨胀变形的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a wide water content original phosphogypsum composite curing agent for road base which can replace gravel aggregate, and raw materials include a composite cementing system, an early strength curing agent, a reinforcing agent, a volume stabilizer, an interface hydrophobic agent, a construction performance adjusting agent, a filler or / and a nano crystal core inducing agent by weight, the composite cementing system is a mixture of slag powder, slaked lime, anhydrous sodium silicate and fly ash, an alkali-slag basic cementing system is formed by the slag powder, the slaked lime, the anhydrous sodium silicate and the fly ash, long-term strength growth framework is provided for a cured body, the early strength curing agent, the reinforcing agent, the volume stabilizer, the interface hydrophobic agent, the filler, the nano crystal core inducing agent and the construction performance adjusting agent are used for composite modification, and a composite function system of 'alkali activation-rapid phosphorus solidification-multi-level filling-precise expansion inhibition-interface hydrophobicity-construction regulation' is jointly constructed, synergistic effect is achieved, direct resource utilization of high-water-content original phosphogypsum without drying and without adding gravel is realized, and technical problems of insufficient strength, poor water resistance and easy expansion deformation of the high-water-content original phosphogypsum when directly used for road base are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of road materials, specifically to a composite curing agent for road base courses and subbase courses of highways at all levels, which can replace sand and gravel aggregates and achieve efficient utilization of undisturbed phosphogypsum solid waste, and is suitable for use as a substitute for sand and gravel aggregates. It also relates to road base course materials and their preparation methods. Background Technology

[0002] Phosphogypsum is a major industrial solid waste generated by the phosphate fertilizer industry, with a huge annual stockpile and a low comprehensive utilization rate. Raw phosphogypsum has a wide range of moisture content fluctuations and is generally high (15%–30%). Its particles are ultra-fine, have a large specific surface area, and are highly hydrophilic. Furthermore, it is rich in soluble sulfates, phosphates, and fluorides. Direct use in road engineering presents the following drawbacks: it is prone to saturation and softening under high moisture content, easily forming springy soil during compaction, making it difficult to meet the compaction requirements of highway base course specifications; while existing technologies use curing agents to stabilize phosphogypsum, single curing agents such as cement and lime have limited functions, only improving early strength and failing to break the continuous water film on the surface of phosphogypsum particles, resulting in poor anti-slip and anti-rebound capabilities; moreover, sulfates in the system easily cause later volume expansion, pavement bulging and cracking, and insufficient long-term stability; it also has poor water resistance, easily softening and disintegrating when soaked in water. If a compound of various conventional curing agents is used, such as a conventional compound system of cement, slag, fly ash, and lime, there will be a serious problem of component homogenization. Furthermore, it cannot meet the requirements of working conditions with a wide range of moisture contents, and it cannot systematically solve the problem of soluble phosphorus and fluorine in phosphogypsum inhibiting hydration. Therefore, when high-moisture-content undisturbed phosphogypsum is directly used for road base courses, it will suffer from insufficient strength, poor water resistance, and easy expansion and deformation, and it cannot be used to replace sand and gravel aggregates.

[0003] Therefore, it is necessary to solve the technical problems of insufficient strength, poor water resistance, and easy expansion and deformation when high-water-content undisturbed phosphogypsum is directly used in road base courses. Summary of the Invention

[0004] In view of this, the purpose of the present invention is to provide a wide-moisture undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates, road base course materials and their preparation methods. The curing agent stabilizes phosphogypsum, effectively improving the strength, water stability, anti-expansion performance and long-term stability of the cured phosphogypsum, so that undisturbed phosphogypsum can be directly used in road base courses to replace sand and gravel aggregates and meet the various performance requirements of road base courses.

[0005] The present invention relates to a wide-water-ratio undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates. The raw materials of the composite curing agent include the following components by weight: 60-92 parts of composite cementitious system, 2-5 parts of early-strength curing agent, 14.5-20.7 parts of reinforcing agent, 1-1.8 parts of volume stabilizer, 1.5-2.5 parts of interface hydrophobic agent, 3-8 parts of filler, 0-3 parts of nanocrystal nucleation inducer, and 0.35-1 part of construction performance regulator. The composite cementitious system is a mixture of slag powder, hydrated lime, anhydrous sodium silicate, and fly ash.

[0006] Furthermore, in the composite cementitious system, by weight, there are 40-55 parts of slag powder, 10-15 parts of hydrated lime, 5-10 parts of anhydrous sodium silicate, and 5-12 parts of fly ash.

[0007] Furthermore, the reinforcing agent is a mixture of metakaolin and nano-silica, with 14-20 parts metakaolin and 0.5-0.7 parts nano-silica by weight.

[0008] Furthermore, the early-strength coagulating agent is calcium formate, and the volume stabilizer is one or both of calcium metaborate and anhydrous calcium borate.

[0009] Furthermore, the interface hydrophobic agent is one or two of calcium stearate and sodium stearate, and the filler is ultrafine silica fume;

[0010] Furthermore, the nanocrystal nucleus inducer is oligomeric calcium silicate, and the construction performance regulator is a mixture of disodium EDTA and polycarboxylate superplasticizer, with 0.05-0.2 parts by weight of disodium EDTA and 0.3-0.8 parts by weight of polycarboxylate superplasticizer.

[0011] The present invention also discloses a road base material, which uses undiluted phosphogypsum to replace sand and gravel aggregates. The raw materials of the road base material include the following components by weight: 84-90 parts of undiluted phosphogypsum, 5-8 parts of cement, and 5-8 parts of the composite curing agent as described in claim 1.

[0012] This invention also discloses a method for preparing a road base material, comprising the following steps:

[0013] S1, dry mix cement with a composite curing agent of undisturbed phosphogypsum with a wide water content that can replace sand and gravel aggregates for road base, and obtain mixed cementitious powder.

[0014] S2, after mixing the mixed gelling powder with the original phosphogypsum evenly, simmer the mixture to obtain the mixture;

[0015] S3, add water to the mixture and mix to adjust the moisture content.

[0016] Furthermore, in step S2, the simmering time is 30 to 60 minutes;

[0017] Furthermore, in step S3, the moisture content is adjusted to 25-32%.

[0018] The beneficial effects of this invention are as follows: This invention relates to a wide-moisture content undisturbed phosphogypsum composite curing agent, road base material, and preparation method for road base courses that can replace sand and gravel aggregates. It utilizes an alkali-slag-based cementitious system composed of slag powder, hydrated lime, anhydrous sodium silicate, and fly ash to provide a long-term strength growth framework for the solidified body. It further employs early-strength curing agents, reinforcing agents, volume stabilizers, interface hydrophobic agents, fillers, nanocrystalline nuclei inducers, and construction performance regulators for composite modification, collectively constructing a composite functional system of "alkaline activation - rapid phosphogypsum fixation - multi-stage filling - precise swelling suppression - interface hydrophobicity - construction control." This synergistic effect enables the direct resource utilization of high-moisture content undisturbed phosphogypsum without drying or adding sand and gravel, solving the technical problems of insufficient strength, poor water resistance, and easy expansion and deformation when high-moisture content undisturbed phosphogypsum is directly used in road base courses. Detailed Implementation

[0019] To better understand the present invention, the following embodiments are further illustrations of the present invention, but the content of the present invention is not limited to the following embodiments.

[0020] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0021] This embodiment describes a wide-moisture-ratio undisturbed phosphogypsum composite curing agent for road base courses, which can replace sand and gravel aggregates. The raw materials of the composite curing agent, by weight, include the following components: 40-55 parts slag powder, 10-15 parts hydrated lime, 5-10 parts anhydrous sodium silicate, 5-12 parts fly ash, 2-5 parts early-strength coagulant, 14-20 parts metakaolin, 0.5-0.7 parts nano-silica, 1-1.8 parts volume stabilizer, 1.5-2.5 parts interface hydrophobic agent, 3-8 parts filler, 0-3 parts nano-crystal nucleation inducer, and E... Disodium DTA 0.05–0.2 parts, polycarboxylate superplasticizer 0.3–0.8 parts; slag powder, hydrated lime, anhydrous sodium silicate, and fly ash constitute an alkali-slag cementitious system. Hydrated lime provides an alkaline environment, and anhydrous sodium silicate activates the pozzolanic activity of slag powder and fly ash, generating CSH gel and CASH gel, providing a long-term strength growth framework for the solidified body; calcium formate is preferred as an early-strength phosphorus fixative. Hydrated lime first provides a strongly alkaline environment (pH≥11). Under these alkaline conditions, calcium formate rapidly dissolves and releases calcium ions (Ca). 2+ ) and formate ions (HCOO) - The released calcium ions react with the soluble phosphate ions (PO4) dissolved in the phosphogypsum. 3- HPO4 2-The reaction produces hydrated calcium phosphate salts (such as calcium phosphate rock CaHPO4·2H2O), which may further transform into low-solubility hydroxyapatite, thus efficiently fixing phosphorus impurities and eliminating the inhibition of subsequent hydration reactions by phosphate ions. Simultaneously, formate ions promote the hydration of cement clinker minerals, accelerating the early hydration of C3S and C3A, forming an early strength framework, and overcoming the shortcomings of slow reaction and strong encapsulation effect of the lime precipitation method.

[0022] Multi-scale reinforcement using metakaolin + nano silica: nano SiO2 provides an ultrafine nucleation effect, and metakaolin generates C-(A)-SH gel in an alkaline environment. The two form a continuous dense structure from nano to micron, which significantly improves density and crack resistance.

[0023] Calcium metaborate exhibits volume stability: Under the alkaline environment provided by slaked lime (measured pH ≥ 11), calcium metaborate slowly releases borate ions (B4O7). 2- ), and Ca 2+ The formation of calcium borate complexes regulates the hydration rate of calcium aluminate in cement, inhibiting excessive formation of ettringite (AFt) in the later stages, thereby effectively controlling expansion. Compared with conventional expansion inhibitors such as borax, calcium metaborate has the advantage that while borax can delay hydration by forming a calcium borate coating, the coating layer is prone to becoming too thick, significantly hindering later strength development (Table 5 confirms a 20.8% decrease in strength at 28 days in the borax group); while calcium metaborate has a more moderate slow-release characteristic, neither excessively inhibiting hydration at the same dosage nor failing to regulate AFt formation over a long period, thus achieving the unique effect of "controlling expansion without reducing strength". It should be noted that although calcium metaborate is known to have an expansion-inhibiting effect in the prior art, its slow-release behavior is limited in the acidic undisturbed phosphogypsum environment without pH adjustment, and its strength is insufficient when used alone. This invention pre-adjusts the system to a strongly alkaline state using slaked lime, creating the necessary conditions for calcium metaborate to exert its optimal inhibitory effect. This invention pre-neutralizes acidity and fixes soluble phosphorus with calcium formate, objectively creating an alkaline environment where calcium metaborate exerts its inhibitory effect, thus forming a functional chain of "pretreatment + inhibition". In addition, expansion inhibitors (borax, aluminum sulfate, citric acid, etc.) are also used in the field of phosphogypsum road base curing. However, while commonly used expansion inhibitors have a certain anti-expansion effect, their application to road base materials leads to a significant decrease in strength.

[0024] The invention employs a synergistic approach of interfacial hydrophobicity and dual densification using calcium stearate / sodium stearate: Calcium stearate / sodium form a directionally adsorbed hydrophobic film on the surface of phosphogypsum particles, significantly reducing the water absorption rate of the material's pores, which is the direct reason for the improved softening coefficient. More importantly, in the system of this invention, the hydrophobic effect of calcium stearate / sodium, combined with the multi-level filling and densification structure constructed from metakaolin, nano-silica, and ultrafine silica fume, forms a "dual densification-hydrophobic synergy." On the one hand, the multi-level filling significantly reduces the number of interconnected capillaries; on the other hand, the hydrophobic film reduces the water absorption tendency of the remaining closed pores. The combination of these two factors results in a significantly higher softening coefficient in the solidified body even without the addition of calcium metaborate (Comparative Example C8) compared to existing technologies. The addition of calcium metaborate (Comparative Example C6) further suppresses microcracks that may be generated due to slight expansion in the later stages of hydration, making the material structure more complete. Therefore, the softening coefficient is increased from 0.84 to 0.86, achieving a further improvement in water resistance.

[0025] Construction performance was adjusted using disodium EDTA and polycarboxylate superplasticizer: disodium EDTA complexes high-valence metal ions (Fe). 3+ Al 3+ (etc.), eliminating its competitive adsorption on polycarboxylate superplasticizer, ensuring that the superplasticizer fully exerts its dispersing effect. Ultrafine silica fume is used for compaction: ultrafine silica fume fills micron-level pores, further improving the compactness.

[0026] Calcium oligosilicate can be selected as the nanocrystal nucleus induction agent: Unlike cement concrete systems, phosphogypsum systems are weakly acidic (pH 4.0–7.5), and the stability of conventional CSH crystal nuclei decreases in acidic environments. This invention provides an alkaline environment (pH ≥ 11) using slaked lime, while calcium formate fixes soluble phosphorus, allowing the calcium oligosilicate crystal nuclei to exist stably and exert a nano-induced hydration effect, further accelerating the nucleation and growth of hydration products. This, combined with the macroscopic reinforcement of calcium formate and metakaolin, forms a multi-scale synergistic effect.

[0027] In this embodiment, to further optimize the synergistic effect among the components, the following ratio relationship is preferably satisfied between the above components:

[0028] (1) The preferred dosage of the oligomeric calcium silicate is 1 to 3 parts;

[0029] (2) Calcium formate, metakaolin and calcium metaborate constitute a "phosphorus fixation-enhancement-inhibition" functional chain: quicklime provides an alkaline environment (pH≥11), under which calcium formate fixes soluble phosphorus, providing conditions for the volcanic ash reaction of metakaolin and the expansion inhibition of calcium metaborate. All three are indispensable.

[0030] (3) The mass ratio of metakaolin to nano silica is (20-40):1. Within this range, the nanoparticles are uniformly dispersed in the metakaolin matrix, forming a continuous and dense filling structure from nano to micron level, with the best synergistic enhancement effect.

[0031] (4) The mass ratio of calcium formate to calcium metaborate is (1.1-5):1, and the two work together to control early phosphorus fixation and later expansion.

[0032] In this embodiment, the slag powder has a specific surface area ≥400m² / kg, an activity index ≥95%, an SO3 content ≤4.0%, and a moisture content ≤1.0%; the hydrated lime has an effective CaO+MgO content ≥85%, and a fineness of ≤10% residue on a 0.08mm square-hole sieve; the anhydrous sodium silicate has a modulus of 1.0~3.3, an effective content ≥98%, and a moisture content ≤1.0%.

[0033] Fly ash should have the following properties: fineness (residue ≤45% on a 0.045mm square-hole sieve), loss on ignition ≤8.0%, and activity index ≥70%; effective content of calcium formate ≥98%, with residue ≤5% on a 200-mesh sieve; metakaolin should have an activity index ≥110% and a specific surface area ≥10000m² / kg; effective content of calcium stearate or sodium stearate ≥98%, with residue ≤5% on a 200-mesh sieve; and effective content of calcium metaborate or anhydrous calcium borate ≥98%, with a moisture content ≤1.0%. The specific surface area of ​​nano-silica is ≥15000m² / kg, SiO2 content is ≥99%, and moisture content is ≤1.0%; the SiO2 content of ultrafine silica fume is ≥85%, the specific surface area is ≥15000m² / kg, and the moisture content is ≤1.0%; the solid content of polycarboxylate superplasticizer is ≥98%, the water reduction rate is ≥25%, and it is chlorine-free and sodium sulfate-free; the effective content of disodium EDTA is ≥99%; the solid content of oligomeric calcium silicate is ≥95%, and the average particle size is ≤100nm.

[0034] This embodiment also discloses a road base material, which uses undisturbed phosphogypsum to replace sand and gravel aggregates. The raw materials of the road base material include the following components by weight: 84-90 parts of undisturbed phosphogypsum, 5-8 parts of cement, and 5-8 parts of the composite curing agent as described in claim 1. The cement is P·O 42.5 ordinary Portland cement, which meets the requirements of GB175. The undisturbed phosphogypsum is characterized by: a moisture content of 15%-30%, a pH value of 4.0-7.5, a soluble sulfate content of ≤2.0%, a fineness of ≤30% residue on a 0.15mm square-hole sieve, and an organic matter content of ≤3.0%. It requires no drying or water washing pretreatment.

[0035] This embodiment also discloses a method for preparing a road base material, including the following steps:

[0036] S1, dry mix cement with a composite curing agent of undisturbed phosphogypsum with a wide water content that can replace sand and gravel aggregates for road base, and obtain mixed cementitious powder.

[0037] S2, after mixing the mixed gelling powder with the original phosphogypsum evenly, let it sit for 30 min to 60 min to ensure that the phosphorus fixation reaction is fully carried out, and the mixture is obtained.

[0038] S3, add water to the mixture and adjust the moisture content to 25-32%; the mixing water should be groundwater or domestic water, with a pH of 5.0-9.0, insoluble matter ≤2000mg / L, and SO42-. 2- ≤800mg / L.

[0039] Example 1

[0040] The phosphogypsum road base layer in this embodiment uses a composite curing agent that does not contain calcium oligosilicate.

[0041] First, weigh the following components of the composite curing agent according to weight: 45 parts slag powder, 13.4 parts hydrated lime, 8.0 parts anhydrous sodium silicate, 5 parts fly ash, 4.0 parts calcium formate, 16 parts metakaolin, 1.5 parts calcium metaborate, 2.0 parts calcium stearate, 0.5 parts nano silica, 4 parts ultrafine silica fume, 0.5 parts polycarboxylate superplasticizer, and 0.1 parts disodium EDTA, for a total of 100 parts. Put them into a dry powder mixer and mix evenly to obtain the composite curing agent.

[0042] Then, weigh out 87 parts of undisturbed phosphogypsum (25% moisture content), 6 parts of P·O 42.5 cement, and 7 parts of composite curing agent according to the weight ratio. Dry mix the cement and composite curing agent evenly to obtain a mixed cementitious powder. Add the mixed cementitious powder to the undisturbed phosphogypsum and mix evenly on the construction site. Let it sit for 45 minutes. Finally, add water to adjust to the optimal moisture content (28% as determined by compaction test). Spread, statically press to shape, weakly vibrate to compact, statically press to finish, and cover with a film for 7 days to retain moisture and cure, thus obtaining the phosphogypsum road base material.

[0043] The performance of this phosphogypsum road base material was tested using conventional methods in the existing technology, and the test results are as follows:

[0044] The 7-day unconfined compressive strength is 3.5 MPa, the 28-day strength is 5.6 MPa, the water softening coefficient is 0.86, the drying shrinkage coefficient is 0.17%, the 180-day expansion rate is 0.07%, the compaction degree is 98.3%, and the total phosphorus in the leachate is 7 mg / L.

[0045] Example 2

[0046] The phosphogypsum road base layer in this embodiment uses a composite curing agent containing oligomeric calcium silicate:

[0047] First, weigh the following components of the composite curing agent according to weight: 43 parts slag powder, 13 parts hydrated lime, 8 parts anhydrous sodium silicate, 5 parts fly ash, 4 parts calcium formate, 16 parts metakaolin, 2.0 parts calcium stearate, 1.6 parts calcium metaborate, 0.5 parts nano silica, 4 parts ultrafine silica fume, 0.5 parts polycarboxylate superplasticizer, 0.1 parts disodium EDTA, and 2.3 parts oligomeric calcium silicate, for a total of 100 parts. Put them into a dry powder mixer and mix evenly to obtain the composite curing agent.

[0048] Then, weigh out 87 parts of undisturbed phosphogypsum (moisture content 25%), 6 parts of P·O 42.5 cement, and 7 parts of composite curing agent according to weight. Dry mix the cement and composite curing agent evenly to obtain a mixed cementitious powder. Add the mixed cementitious powder to the undisturbed phosphogypsum and mix evenly on the construction site. Let it sit for 45 minutes. Finally, add water to adjust to the optimal moisture content (determined to be 28% by compaction test). Spread, statically press to shape, weakly vibrate to compact, statically press to finish the surface, and cover with a film for 7 days to keep it moist and cured, thus obtaining the phosphogypsum road base material.

[0049] The performance of this phosphogypsum road base material was tested using conventional methods in the existing technology, and the test results are as follows:

[0050] The 7-day unconfined compressive strength is 3.8 MPa, the 28-day strength is 6.0 MPa, the water softening coefficient is 0.88, the drying shrinkage coefficient is 0.15%, the 180-day expansion rate is 0.06%, the compaction degree is 98.8%, and the total phosphorus in the leachate is 6 mg / L.

[0051] Example 3

[0052] In this embodiment, the phosphogypsum road base layer uses a high moisture content condition with low-polysilicate calcium:

[0053] First, weigh the following components of the composite curing agent according to weight: 43.5 parts slag powder, 12.0 parts hydrated lime, 7.0 parts anhydrous sodium silicate, 5.0 parts fly ash, 4.5 parts calcium formate, 17.0 parts metakaolin, 2.0 parts sodium stearate, 1.5 parts anhydrous calcium borate, 0.6 parts nano silica, 4.0 parts ultrafine silica fume, 0.5 parts polycarboxylate superplasticizer, 0.1 parts disodium EDTA, and 2.3 parts oligomeric calcium silicate, for a total of 100 parts. Add these components to a dry powder mixer and mix evenly to obtain the composite curing agent.

[0054] Then, weigh out 90 parts of undisturbed phosphogypsum (30% moisture content), 5 parts of P·O 42.5 cement, and 5 parts of composite curing agent according to the weight ratio. Dry mix the cement and composite curing agent evenly to obtain a mixed cementitious powder. Add the mixed cementitious powder to the undisturbed phosphogypsum and mix evenly on the construction site. Let it sit for 60 minutes. Since the initial moisture content is close to the optimum moisture content (30%), there is no need to add water. Directly spread, statically press to shape, weakly vibrate to compact, statically press to finish the surface, and cover with a film to keep it moist for 7 days to obtain the phosphogypsum road base material.

[0055] The performance of this phosphogypsum road base material was tested using conventional methods in the existing technology, and the test results are as follows:

[0056] The 7-day unconfined compressive strength is 3.8 MPa, the 28-day strength is 5.8 MPa, the water softening coefficient is 0.87, the drying shrinkage coefficient is 0.13%, the 180-day expansion rate is 0.06%, the compaction degree is 97.0%, and the total phosphorus in the leachate is 6 mg / L.

[0057] Example 4

[0058] In this embodiment, the phosphogypsum road base layer uses a high moisture content condition with low-polysilicate calcium:

[0059] First, weigh the following components of the composite curing agent according to their weight: 45.0 parts slag powder, 14.0 parts hydrated lime, 9.0 parts anhydrous sodium silicate, 6.0 parts fly ash, 3.0 parts calcium formate, 14.0 parts metakaolin, 1.8 parts calcium stearate, 1.3 parts calcium metaborate, 0.4 parts nano silica, 3.5 parts ultrafine silica fume, 0.4 parts polycarboxylate superplasticizer, 0.1 parts disodium EDTA, and 1.5 parts oligomeric calcium silicate, for a total of 100 parts. Add these components to a dry powder mixer and mix thoroughly to obtain the composite curing agent.

[0060] Then, weigh out 89 parts of undisturbed phosphogypsum (20% moisture content), 5.5 parts of P·O 42.5 cement, and 5.5 parts of composite curing agent according to weight. Dry mix the cement and composite curing agent evenly to obtain a mixed cementitious powder.

[0061] The mixed cementitious powder was added to the undisturbed phosphogypsum and forcibly mixed evenly on site, then left to stand for 30 minutes. Finally, water was added to adjust to the optimal moisture content (24% as determined by compaction test), and the mixture was spread, statically pressed to shape, lightly vibrated to compact, and statically pressed to finish. It was then covered with a film for 7 days to maintain moisture and obtain the phosphogypsum road base material.

[0062] The performance of this phosphogypsum road base material was tested using conventional methods in the existing technology, and the test results are as follows:

[0063] Performance test results: 7-day unconfined compressive strength 3.4 MPa, 28-day strength 5.6 MPa, water softening coefficient 0.86, drying shrinkage coefficient 0.19%, 180-day expansion rate 0.10%, compaction degree 98.0%, and total phosphorus in leachate 7 mg / L.

[0064] Comparative Example 1: Basic Synergistic Effect Comparison Experiment

[0065] To verify the synergistic effect of the key components of this invention (calcium formate, metakaolin, calcium metaborate, and disodium EDTA), the following comparative examples were set up. All experiments used the same undisturbed phosphogypsum with a moisture content of 25%, P·O 42.5 cement, and the same curing regime and testing methods. The total dosage of each curing agent was 7% (i.e., 87 parts undisturbed phosphogypsum, 6 parts cement, and 7 parts composite curing agent, totaling 100 parts). The internal proportions of the composite curing agent were prepared according to Table 1 below:

[0066]

[0067] ① Note: Control group C1 was prepared according to the conventional phosphogypsum curing agent formulation in this field. The main components and contents are: 40 parts cement, 30 parts slag powder, 12 parts lime, 8 parts sodium silicate, and 10 parts fly ash, with a total of 100 parts, namely: 40% cement, 30% slag powder, 12% lime, 8% sodium silicate, and 10% fly ash.

[0068] Comparative Example 2

[0069] Critical value test

[0070] To demonstrate the functionality and non-arbitrariness of the component range defined in this invention (2-5 parts calcium formate, 1.0-1.8 parts calcium metaborate, and 0.05-0.2 parts disodium EDTA; since the total amount is 100 parts, the percentages are 2-5% calcium formate, 1.0-1.8% calcium metaborate, and 0.05-0.2% disodium EDTA), the following critical value control experiments were conducted, all based on the control example C6 formulation (basic formulation, without oligomeric calcium silicate), with only the dosage of a single component changed. The experimental results are shown in Table 3. Simultaneously, to verify the critical synergistic characteristics of disodium EDTA, a gradient experiment of disodium EDTA dosage (0%, 0.02%, 0.05%, 0.08%, 0.10%, 0.15%) was supplemented, and the results are shown in Table 4 below.

[0071] Table 3 shows that when calcium formate content is below 2%, soluble phosphorus fixation is incomplete (total phosphorus in the leachate increases from 7 mg / L to 25 mg / L), and the 28-day strength decreases from 5.5 MPa to 3.8 MPa, failing to meet the requirements for highway base courses. When calcium metaborate content is below 1.0% (critical group B), the 180-day expansion rate surges from 0.09% to 0.38%, exceeding the allowable range for highway engineering. It is noteworthy that calcium metaborate primarily affects volume stability and has no direct contribution to soluble phosphorus fixation; therefore, the total phosphorus in the leachate of critical group B remains at 7 mg / L (the same as control example C6). However, the significant increase in expansion rate leads to an increase in internal microcracks, causing the 28-day strength to decrease slightly from 5.5 MPa to 5.2 MPa. If the curing period is extended, the strength decrease will be more significant. This further proves that the calcium metaborate content must be ≥1.0%. Table 4 shows that when the EDTA disodium content increases from 0.02% to 0.05%, the compaction degree jumps from 97.2% to 98.0%, and the 28-day strength increases from 5.4 MPa to 5.5 MPa; at a content of 0.08%, the compaction degree reaches 98.3% and the strength is 5.55 MPa; at 0.10%, the compaction degree is 98.5% and the strength is 5.6 MPa; and at 0.15%, the performance tends to stabilize. This indicates that 0.05% is the lower limit of the EDTA disodium content for significant synergistic effects; below this value, the effect is weak and cannot meet engineering requirements. After EDTA disodium complexes with high-valence metal ions, the polycarboxylate superplasticizer can fully exert its dispersing effect, significantly improving the workability of the mixture, thereby achieving higher density and compaction degree under the same compaction work. When the content of disodium EDTA is below 0.05% (critical group C, 0.02% and the 0.02% group in Table 4), the highest compaction degree is only 97.1%, and the strength is ≤5.3 MPa, both lower than that of control example C6 (98.3% / 5.5 MPa), indicating that optimal performance cannot be achieved. Table 4 further confirms that 0.05% is the lower limit critical point for disodium EDTA to exert a significant synergistic effect. This fully demonstrates that the dosage range of each component defined in this invention has a clear functional boundary and is not a conventional choice.

[0072] Comparative Example 3

[0073] Comparison with known swelling inhibitors

[0074] To demonstrate the non-obvious comprehensive technical advantages of calcium metaborate in the system of this invention, using Control Example C6 (basic formulation) as a benchmark, Control Example C7 was prepared by replacing calcium metaborate (1.5%) with borax (Na2B4O7·10H2O), the most commonly used expansion inhibitor in the art, while keeping other components unchanged, for performance comparison. Simultaneously, Control Example C8 was set up without any expansion inhibitor (calcium metaborate was removed, and the remaining components were scaled up to 100%). The results are shown in Table 5.

[0075] Table 5 shows that while borax can inhibit expansion to some extent (0.58%→0.23%), it leads to a 20.8% decrease in strength (5.3MPa→4.2MPa), a decrease in the softening coefficient to 0.74, and an increase in the drying shrinkage coefficient by 0.12%. In contrast, calcium metaborate in the specific "calcium formate-metakaolin-hydrated lime" system of this invention effectively controls expansion (0.09%) while maintaining a 28-day strength of 5.5MPa (slightly higher than the 5.3MPa of the group without inhibitor), a softening coefficient of 0.86 (higher than the 0.74 of the borax group), and a drying shrinkage coefficient of 0.18 (significantly better than the 0.31 of the borax group), achieving the unique effect of "controlling expansion without reducing strength". It is well known to those skilled in the art that in cement-based or gypsum-based materials, any expansion inhibitor inevitably sacrifices a certain amount of strength. However, the data in Table 5 of this invention unexpectedly shows that while calcium metaborate suppressed the expansion rate from 0.58% to 0.09% (a reduction of 84%), the 28-day strength actually increased slightly from 5.3 MPa to 5.5 MPa. This unconventional phenomenon of "controlled expansion without reduced strength" was unforeseen. This fully demonstrates that calcium metaborate in the system of this invention produces a comprehensive technical effect that cannot be obtained by simple deduction from known expansion inhibitors (borax).

[0076] Comparative Example 4

[0077] Long-term durability test (using control example C6 formulation)

[0078] The results show that the cured body of the present invention not only meets the short-term strength requirements, but also maintains excellent performance under harsh service environments such as freeze-thaw cycles, drying shrinkage, long-term immersion in water, and sulfate attack.

[0079] Comparative Example 5

[0080] Wide moisture content adaptability verification (tested with control example C6 basic formulation)

[0081] To verify the curing adaptability of the present invention to undisturbed phosphogypsum with a wide range of moisture contents, the undisturbed phosphogypsum with different initial moisture contents was directly cured (without drying or adding sand and gravel) using the control example C6 formulation (basic formulation). The 28-day unconfined compressive strength and compaction degree were tested, and verification data for different sources of phosphogypsum (different pH values) were supplemented. The results are shown in Tables 7 and 8.

[0082] In summary, the components of the composite curing agent of this invention have a synergistic effect:

[0083] (1) Synergistic effect of rapid phosphorus fixation and enhancement of calcium formate and metakaolin: The strength of the control group C2 was only 2.0 MPa at 28 days. After adding calcium formate and metakaolin (control group C4), the strength increased to 5.2 MPa at 28 days, an increase of 160%. At the same time, the total phosphorus in the leachate decreased from 68 mg / L to 8 mg / L, a decrease of 88%. This indicates that calcium formate effectively fixes soluble phosphorus by generating permealuminate, creating a phosphorus-free hydration environment for the volcanic ash reaction of metakaolin. Both are indispensable.

[0084] (2) The expansion inhibition of calcium metaborate is irreplaceable: The expansion rate of control group C4 (without calcium metaborate) was 0.58% after 180 days, while the expansion rate of control group C5 (with calcium metaborate added) dropped sharply to 0.12%, a decrease of 79%. However, the strength of calcium metaborate alone (control group C3) was only 2.3 MPa, which could not meet the engineering requirements. Only when calcium formate + metakaolin provides a sufficient strength framework can calcium metaborate fully exert its long-term volume stability regulation effect.

[0085] (3) Critical synergistic effect of disodium EDTA

[0086] Disodium EDTA eliminates the competitive adsorption of high-valence metal ions (Fe³⁺, Al³⁺, etc.) on polycarboxylate superplasticizers by complexing them, thus allowing the superplasticizers to fully exert their dispersion effect. Tables 2 and 4 show that without EDTA, the compaction degree is 97.0% and the strength is 5.2 MPa (C5); with an EDTA content of 0.02% (critical group C), the compaction degree is 97.1% and the strength is 5.3 MPa, showing only a slight improvement; when the content increases to 0.1% (C6), the compaction degree jumps to 98.3% and the strength to 5.5 MPa, demonstrating a significant effect. This indicates that disodium EDTA needs to reach a content of at least 0.05% to fully exert its complexing and synergistic effect; this lower limit has a clear engineering necessity and is not a conventional choice.

[0087] (4) The embodiments of the present invention integrate multiple functional components such as calcium formate, metakaolin, calcium metaborate, nano-silica, and disodium EDTA. Its key indicators such as 28-day strength (5.5 MPa), softening coefficient (0.86), 180-day expansion rate (0.09%), and total phosphorus in leachate (7 mg / L) are significantly superior to any missing group or existing technology, and all performance characteristics simultaneously meet the technical standards for highway base courses. This comprehensive effect of "high strength, high water resistance, high volume stability, and low environmental risk" cannot be expected by simply superimposing the functions of each component, reflecting a non-obvious synergistic effect.

[0088] This invention synergistically utilizes multifunctional components such as calcium formate, metakaolin, nano-silica, calcium metaborate, and disodium EDTA for the curing of phosphogypsum road base layers. Furthermore, it can be further optimized by adding oligomeric calcium silicate, systematically solving core issues such as rapid fixation of soluble phosphorus, construction across wide moisture content ranges, long-term volume stability, and water resistance. It can achieve a phosphogypsum content of 84%–90%, directly curing undisturbed phosphogypsum with a moisture content of 15%–30% without drying, washing, or adding aggregates. The process is simple and low-cost. Compared with existing curing agents, the performance of the cured body of this invention is significantly improved: the 28-day unconfined compressive strength increases from 2.4 MPa to 5.5 MPa–6.0 MPa; the water softening coefficient increases from 0.55 to 0.86–0.88, an increase of 56%–60%; and the 180-day expansion rate decreases from 0.65% to 0.06%–0.10%, a reduction of over 85%. Furthermore, it exhibits excellent long-term durability: Tested using the control formula C6, the strength loss rate after 25 freeze-thaw cycles (28 days) is ≤15%, the 28-day drying shrinkage coefficient is 0.18%, the strength retention rate after 180 days of water immersion is 88%, and the sulfate resistance coefficient (90 days) is 0.96. All durability indicators meet the general technical requirements for relevant durability evaluations. It also boasts significant economic benefits. Compared to existing technologies, this invention eliminates the need for drying or washing pretreatment of phosphogypsum, reducing the processing cost per ton of phosphogypsum by approximately 60-80 yuan; it also eliminates the need for adding sand and gravel aggregate, reducing the cost of road base materials per cubic meter by approximately 40-60 yuan. Based on an annual utilization of 1 million tons of phosphogypsum, this can save approximately 50-80 million yuan in costs.

[0089] This invention solves the technical problem of single-function components sacrificing some benefits through a modular design of "basic cementing components" and "multifunctional composite modified components." The basic cementing components provide a stable framework and alkaline environment; calcium formate removes obstacles for subsequent hydration; metakaolin and nano-SiO2 construct a dense structure; calcium metaborate ensures long-term volume safety; and calcium stearate enhances water resistance and durability. Any change or omission of the component range defined in independent claim 1 will lead to a drastic decrease in overall performance.

[0090] Furthermore, this invention overcomes the technical bias of those skilled in the art who tend to use conventional inhibitors such as borax while neglecting calcium metaborate in the design of phosphogypsum road base curing agents. Through systematic comparative experiments (Table 5), this invention demonstrates that in the specific "calcium formate-metakaolin-hydrated lime" system of this invention, calcium metaborate can produce a superior overall technical effect compared to borax—effectively controlling expansion (reducing it from 0.58% to 0.09%) while increasing the 28-day unconfined compressive strength by approximately 3.8% compared to the group without expansion inhibitors (control example C8). This effect cannot be derived from the conventional performance of known expansion inhibitors (borax, etc.), demonstrating the non-obviousness of this invention.

[0091] Furthermore, this invention is the first to apply calcium oligosilicate nucleating agent to phosphogypsum road base system, and by adjusting the pH to alkaline (≥11) with slaked lime, it solves the technical problem of instability of calcium oligosilicate in acidic phosphogypsum environment, and realizes the multi-scale synergistic enhancement effect of nanocrystalline nucleus-induced hydration.

[0092] The solidified body of this invention is an inorganic binder-stabilized fine-grained material. The compaction degree reaches over 95% under various moisture content conditions, meeting the compaction requirements (≥95%) for subbase courses of expressways and Class I highways, as well as base courses and subbase courses of Class II and lower highways, as specified in the "Technical Specifications for Construction of Highway Pavement Base Courses" (JTG / T F20-2015). The corresponding 7-day unconfined compressive strength is 3.0–3.9 MPa, meeting the strength requirements of JTG / T F20-2015 for subbase courses of medium and light traffic load levels for expressways and Class I highways. If used for expressway / Class I highway base courses, its strength indicators also meet the specifications and can be selected according to the actual engineering conditions. The 28-day unconfined compressive strength of all specimens reached 4.8–6.2 MPa, indicating that the material has excellent late-stage strength development capabilities.

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A wide-moisture-rate undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates, characterized in that: The composite curing agent raw material comprises the following components by weight: 60-92 parts of composite cementitious system, 2-5 parts of early-strength curing agent, 14.5-20.7 parts of reinforcing agent, 1-1.8 parts of volume stabilizer, 1.5-2.5 parts of interface hydrophobic agent, 3-8 parts of filler, 0-3 parts of nanocrystal nucleation inducer, and 0.35-1 part of construction performance regulator. The composite cementitious system is a mixture of slag powder, hydrated lime, anhydrous sodium silicate, and fly ash.

2. The wide-moisture-rate undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates according to claim 1, characterized in that: In the composite cementitious system, by weight, there are 40-55 parts of slag powder, 10-15 parts of hydrated lime, 5-10 parts of anhydrous sodium silicate, and 5-12 parts of fly ash.

3. The wide-moisture-rate undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates according to claim 1, characterized in that: The reinforcing agent is a mixture of metakaolin and nano-silica, with 14-20 parts metakaolin and 0.5-0.7 parts nano-silica by weight.

4. The wide-moisture-rate undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates according to claim 1, characterized in that: The early-strength solidifying agent is calcium formate, and the volume stabilizer is one or both of calcium metaborate and anhydrous calcium borate.

5. The wide-moisture-rate undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates according to claim 1, characterized in that: The interface hydrophobic agent is one or both of calcium stearate and sodium stearate, and the filler is ultrafine silica fume.

6. The wide-moisture-rate undisturbed phosphogypsum composite curing agent for road base courses that can replace sand and gravel aggregates according to claim 1, characterized in that: The nanocrystal nucleus inducer is oligomeric calcium silicate, and the construction performance regulator is a mixture of disodium EDTA and polycarboxylate superplasticizer, with 0.05-0.2 parts by weight of disodium EDTA and 0.3-0.8 parts by weight of polycarboxylate superplasticizer.

7. A road base material, characterized in that: The road base material uses unrefined phosphogypsum to replace sand and gravel aggregates. The raw materials include the following components by weight: 84-90 parts of unrefined phosphogypsum, 5-8 parts of cement, and 5-8 parts of the composite curing agent as described in claim 1.

8. The method for preparing road base material according to claim 7, characterized in that: Includes the following steps: S1, dry mix cement with a composite curing agent of undisturbed phosphogypsum with a wide water content that can replace sand and gravel aggregates for road base, and obtain mixed cementitious powder. S2, after mixing the mixed gelling powder with the original phosphogypsum evenly, simmer the mixture to obtain the mixture; S3, add water to the mixture and mix to adjust the moisture content.

9. The method for preparing road base material according to claim 8, characterized in that: In step S2, simmer the ingredients for 30 to 60 minutes.

10. The method for preparing road base material according to claim 8, characterized in that: In step S3, the moisture content is adjusted to 25-32%.